Evolving Monetary/Fiscal Policy Mix in the United States - Bianchi, Francesco (American Economic Review, 2012)
A micro-founded model that allows for changes in the monetary/fiscal policy mix and in the volatility of structural shocks is fit to US post-WWII data. Agents are aware of the possibility of regime changes and their beliefs have an impact on the law of motion of the macroeconomy. The results show that the '60s and the '70s were characterized by a prolonged period of active fiscal policy and passive monetary policy. The appointment of Volcker marked a change in the conduct of monetary policy, but it took almost ten years for the fiscal authority to start accommodating this regime change.